BRAND INTERNAL COMMUNICATIONS CULTURE (BICCU) KOTA MALANG - Widayati, Sri; Naha, Rambu (Universitas Merdeka Malang, 2016)
Abstract Malang is a city that has a very heterogeneous population, because immigrants not only came from the city on the island of Java, but from outside of Java Island. Many impacts would arise as a result of the influx of immigrants from all parts of the ground water. The negative impact is most likely to occur is the cultural frictions due to different understandings. Multicultural education that had been made by various parties apparently not able to reduce the cultural misunderstandings. Especially during the activities undertaken to harmonize inter-ethnic conducted by various social organizations partially, has not been well integrated and focused, therefore, the government should be able to make such programs have become a government program ongoing to establish Brand Internal Communications Culture (BICCU). The future is expected BICCU able to form a positive image of Malang as the City Multi ethnic harmonious and hamonis. This activity should be done in an integrated manner by all areas of the City Government of Malang who continue to coordinate with the social institutions, which is already capable of conducting union of multiculture significantly.DOI :Â https://doi.org/10.26905/nomosleca.v2i2.624